Increasing the Reinforcing Value of Exercise in Overweight Adults - Flack, Kyle D.; Ufholz, Kelsey; Johnson, LuAnn; Roemmich, James N. (Frontiers in Behavioral Neuroscience, 2019)
Objectives: This study determined whether a moderate- or high-dose exercise program increases exercise reinforcement. Increasing the relative reinforcing value of exercise (RRVexercise) (i.e., incentive sensitization of exercise) may increase usual physical activity participation. Preference and/or tolerance for the intensity of exercise was also assessed. Design: Sedentary men and women (BMI: 25-35 kg/m2) were randomized into parallel exercise training groups expending either 300 (n=18) or 600 (n=18) kcal/exercise session, five sessions/week, for 12 weeks. Methods: The RRVexercise was determined by how much work was performed for exercise relative to a sedentary alternative in a progressive ratio schedule task. Preference and tolerance for exercise intensity were determined by questionnaire. Results: RRVexercise increased (P<0.05) in both groups. Exercise reinforcement, defined as the amount of work completed for exercise without taking sedentary activity into account, increased (P<0.01) in the 600kcal group only. Preference and tolerance for exercise intensity increased (P<0.01) in both groups, which predicted increases in RRVexercise. Conclusion: Expending 300 or 600 kcal, five days/week increases RRVexercise, while 600 kcal, five days/week may be needed to increase exercise reinforcement.